Irreversibility and hydrothermal analysis of the MWCNTs/GNPs-based nanofluids for electronics cooling applications of the pin-fin heat sinks: Multiphase Eulerian-Lagrangian modeling. (March 2022) - Ambreen, Tehmina; Saleem, Arslan; Tanveer, Muhammad; K, Anirudh; Shehzad, S.A.; Park, Cheol Woo
Abstract: Identifying optimal pin-fin configurations is essential to analyze the full potential of utilizing nanofluids in pin-fin heat sinks for electronics cooling applications. Therefore, the present study aimed to investigate the entropy generation and hydrothermal characteristics of water-based MWCNT (Multiwalled carbon nanotubes) and MWCNT/GNP (Multiwalled carbon nanotubes/graphene nanoplatelets) nanofluids in a heat sink equipped with fins of different configurations. The forced convection of the nanofluid was simulated through the multiphase Eulerian-Lagrangian model (discrete-phase model) by including the influence of slip mechanisms (Brownian motion, thermophoresis, Saffman lift and drag forces, pressure forces, virtual mass, and gravity) and the interphase nanolayering effect. Results showed that the performance of the MWCNT and MWCNT/GNP nanofluids was the highest in the triangular pin-fin heat sink, followed by rhombus and hydrofoil pin-fin heat sinks. The streamlined shape along with the large lateral and small stream-wise interspacing between the hydrofoil and rhombus fins hindered the effective coolant distribution across the heat sinks, thereby deteriorating their heat-dissipation capacity. However, the performance evaluation criteria results of the rhombus pin-fin heat sink outperformed the other pin-fin configurations due to the lower pressure drop. Graphical abstract: Image 1